EFEKTIVITAS PENGGUNAAN MEDIA FLASH CARD DALAM PEMBELAJARAN KANJI MAHASISWA TINGKAT II (2017) PROGRAM STUDI BAHASA JEPANG FKIP UNIVERSITAS RIAU TAHUN 2019 - Nila Septiani; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Media is always to using in learning process, although it’s used in different method. It’s like the writer that used learning aids flash card with cooperative learning method in kanji course. The purpose of this research is to describe how effective by using flash card media in kanji learning students level II of Japanese language education Study Program FKIP Riau University. This research was doing in Japanese language education Study Program FKIP Riau University year 2018/2019. This research using experimental design One Group Pre-test – Post-test design, the population is all students level II that take kanji course, and the sample is class B with 33 students. The sample was obtained by using purposive sampling technique, that’s mean the determination of samples have special consideration so that they are appropriate to be a sampled. The data was obtained by giving a test, that is pre-test at the beginning of research and also post-test at the ending of research, and then the result of the test have to processed using SPSS Version 24 IBM For Windows. The based on data analysis it was obtained that the value of the average pre-test is 69 and the value of the average post-test is increased 14 to be 83. That’s mean’s, there is a significant effect by using flash card in kanji learning.Key Words: Kanji, Flash Card, Effectiveness